Learning Model of Discovery Learning in the Formation of Students' Religious Character (Model Pembelajaran Discovery Learning dalam Pembentukan Karakter Religius Siswa) - Siska Damayanti; Chairul Anwar; Ruhban Masykur (Shautut Tarbiyah, 2023)
This article aims to: 1) analyze the implementation of the Discovery Learning Learning Model in the Formation of Students' Religious Character; 2) analyze the impact of the Discovery Learning Learning Model in the Formation of Students' Religious Character. The research was conducted qualitatively with a descriptive approach at SMAN 13 Bandar Lampung, where data was obtained through observation, interviews and documentation studies. The results of the study show that: 1) Implementation of the Discovery Learning Learning Model in the Formation of Students' Religious Character is divided into three stages, namely: a) Planning, which consists of planning in the syllabus and planning in lesson plans, b) Implementation is marked with preliminary activities, core activities and finally the closing activity, c) Closing, namely the decision-making activity there is a joint deliberation, the reaction ends with a greeting; 2) The impact of the Discovery Learning Learning Model in the Formation of Students' Religious Character is student discipline, responsibility, independence, and student habituation. Keywords: Discovery Learning, Religious Character